Effect of titanium dioxide nanoparticle as an additive on the exhaust characteristics of diesel-water emulsion fuel blends. (1st February 2020) - Vellaiyan, Suresh; Subbiah, Arunkumar; Chockalingam, Prabha
Abstract: The present article details the exhaust characteristics of a CI engine fueled with diesel-water emulsion fuel blends and TiO2 nanoadditive incorporated emulsion fuel blends. BD with different concentrations of water and TiO2 nanoparticle were prepared using mechanical agitation, followed by an ultra-sonication process. The physiochemical properties of test fuel were measured based on EN590 standards, and the results show a good agreement with standard limits. The experiments were carried out in a single-cylinder, four stroke, and natural aspirated diesel engine under different BMEP conditions. The emission characteristics of test fuels show that the water emulsified BDs reduce the NOx and smoke emissions. The HC and CO emissions of water emulsified BD are seem to be higher at low-engine loads, and this trend is reversed at high-engine loads. 10% water in BD reduces the EGT by 8.8% at peak BMEP condition. An inclusion of TiO2 nanoparticle significantly improves the exhaust characteristics.